Nordic Student Teachers’ Views on the Most Efficient Teaching and Learning Methods for Species and Species Identification - Irmeli Palmberg; Sirpa Kärkkäinen; Eila Jeronen; Eija Yli-Panula; Christel Persson (MDPI, 2022)
Teachers need knowledge of species and species identification skills for teaching the structure and function of ecosystems, and the principles of biodiversity and its role in sustainability. The aim of this study is to analyze Nordic student teachers’ views on the most efficient methods and strategies to teach and learn species and species identification, and to find some trends about how well their views are reflected in a species identification test. Student teachers in Finland, Norway, and Sweden (N = 426) answered a questionnaire consisting of fixed and open-ended questions, and a species identification test. An analysis of variance, Chi-Square, and t-test were used for quantitative data and an inductive content analysis for qualitative data. Results showed that outdoor teaching and learning methods are more efficient than indoor methods. The majority of student teachers considered outdoor experiential learning with living organisms as the most efficient teaching and learning method. Student teachers who highlighted outdoor experiential learning and outdoor project work as their most efficient methods received significantly better results in the species identification test than the others. Field trips and fieldwork were emphasized as the most important sources in schools and universities, while the internet was the most important source among media. The student teachers underlined teachers’ expertise in the form of in-depth understanding of subjects and supervising skills for efficient teaching both outdoors and indoors. Therefore, teaching and learning of species and species identification as the practical part of biodiversity and sustainability education is emphasized as an integral part of teacher education programs.